MODELING OF WORK DEVICES WITH RPA TEST COMPLEX OMICRON CMC 356 - Pavel Vivchar; Dmitri Oleynikov; Victoria Lyhmanova; Svyatoslav Strakhov; Sergey Jastrebov; Anna Diachenko; Elena Zakharova (Вестник Северо-Кавказского федерального университета, 2022)
This article presents possibilities of OMICRON CMC 356 software and hardware complex for the simulation of digital terminals of relay protection and automation Sirius-2-L. On the basis of the actual characteristics of the head sections offeeders for the city of Mineralnye Vody was developed simulation algorithm of the terminal Sirius-2-L, check the operation of the device protection in the event of damage at different points in the investigated area of the distribution network. According to test results, setting values were evaluated and selected setting values.